Initial material for waxy maize hybrids’ breeding - A. S. Ignatiev; G. Ya. Krivosheev; D. R. Lupinoga (Зерновое хозяйство России)
A waxy maize variety differs from other varieties, as its grain contains only amylopectin starch, which is considered a very valuable product for use in food, technical industry, and medicine. An insufficient amount of initial material hinders the development of Russian waxy maize hybrids. The purpose of the current study was to develop and select self-pollinated lines that could be promising for breeding waxy starchy maize hybrids. The study was carried out in the FSBSI Agricultural Research Center “Donskoy” in 2019–2021. As the initial material there were used 54 new constant self-pollinated waxy maize lines, developed by the standard method. There have been identified such self-pollinated lines as 24/5, 24/18, 24/29(5), 24/78, 25/2(3), 26/8 with 68.1–70.2 % of amylopectin starch. The new lines were characterized by high values of the most important traits, namely seed productivity (0.91–1.75 t/ha), resistance to lodging (0–0.6 % of lodging plants), smut ‘virus’ infection (0–3.6 % of infected plants), low and medium harvesting moisture content of grain (14.7–16.3 %). The identified lines can be recommended for use in crossbreeding programs to develop new waxy maize hybrids. There has been established that amylopectin starch percentage in grain of self-pollinated maize lines negatively correlates with protein percentage (r = –0.55) and oil (r = –0.29), which must be taken into account when selecting for initial material. There has been established a mean positive correlation between starch percentage and seed productivity (r = 0.33) and number of cobs per 1 plant (r = 0.33). The selection of genotypes with high values of these traits has been recommended when developing a starchy initial material of waxy maize.